MEDIA EDUKASI VIDEO SEBAGAI UPAYA PROMOTIF PADA KELUARGA PASIEN DIABETES MELITUS TIPE 2 DI WILAYAH KERJA PUSKESMAS BALEENDAH - Jeri Sofian; Atin Karjatin (Politeknik Kesehatan Kemenkes Bandung, 2025)
Background: The prevalence of diabetes mellitus in Indonesia increased to 11.7% in 2023. In West Java, there are 570,611 recorded cases, with Bandung Regency ranking second highest (59,205 cases), including 1,540 cases at Baleendah Health Centre. Given this high number of cases, it is necessary to provide education through media to prevent further increases. Objective: To determine the effect of developing educational video media on improving promotive knowledge among families of type 2 diabetes mellitus patients using the 4D model approach. Method: The research employed the 4D development model, consisting of define, design, development (with material testing, media testing, small-scale testing, and pre-experimental testing using a one-group pretest-posttest design involving 37 participants), and dissemination. Results: Needs analysis from the preliminary study indicated that the target audience required educational media in the form of real-life video combined with animated elements. Based on statistical testing, the educational video was declared feasible and effective in increasing participants’ knowledge. The educational video can be accessed at https://youtu.be/uHDU5R7ZntQ?si=KQMpQX2nJ2ENGAuV. Conclusion: The educational video can be utilised as a health promotion medium for promotive efforts related to type 2 diabetes mellitus.